Effects of sea‐level rise and storm‐enhanced flooding on Pacific harbour seal habitat: A comparison of haul‐out changes at the Russian and Eel river estuaries. Issue 7 (11th April 2021) - Backe, Karen; Hines, Ellen; Nielsen, Karina J.; George, Doug; Twohy, Elinor; Lowry, Mark
Abstract: Patterns and changes in the distribution of coastal marine mammals can serve as indicators of environmental change that fill critical information gaps in coastal and marine environments. Coastal habitats are particularly vulnerable to the effects of near‐term sea‐level rise. In California, Pacific harbour seals ( Phoca vitulina richardii ) are a natural indicator species of coastal change because of their reliance on terrestrial habitats, abundance, distribution, and site fidelity. Pacific harbour seals are marine top predators that are easily observed while hauled out at terrestrial sites, which are essential for resting, pupping, and moulting. Although increasing inundation from recent sea‐level rise and storm‐driven flooding has changed the Californian coastline, little is known about the effect of future sea‐level rise and increased storm frequency and strength on harbour seal haulout site availability and quality in California. Harbour seal habitat was modelled at two sandbar‐built estuaries under a series of likely sea‐level rise and storm scenarios. The model outputs suggest that, over time, habitat at both estuaries decreased with increasing sea level, and storm‐enhanced water levels contributed significantly to habitat flooding. These changes reflect pressures on coastal habitats that have an impact on human and natural systems.